Applied evolutionary biology could aid management of invaded ecosystems. Issue 6 (13th August 2015) - Oduor, Ayub M. O.; Yu, Xiubo; Liu, Jian
Abstract : Invasive plant species subvert essential ecosystem services through a reduction in the abundance and genetic diversity of native plant species. A major challenge now facing land managers and policy makers is how to ensure persistence of native plants while limiting harmful impacts of invasions. Results from recent empirical studies suggest that native plants may evolve adaptations to invasive plants and that adaptive evolution in invasive plants could lessen the negative impacts of invasions. Here, we suggest ways in which knowledge of adaptive evolution in invasive and native plants could be utilized to more effectively manage invaded ecosystems.